Effect of Strobilanthes crispa (Keji Beling) Ethanol Extract (EESC) on Body Weight in High-Fat Diet-Induced Wistar Rats - Suandy; Sun, Michelle Angelia; Ana Fresia (Jurnal Kedokteran Brawijaya, 2026)
Obesity is a growing global health concern and a major risk factor for metabolic diseases. Pharmacological therapies have limitations and adverse effects. Strobilanthes crispa has demonstrated pharmacological activities. However, its ethanol extract has not been extensively evaluated for body weight effects in high-fat diet (HFD)-induced rats. This study aimed to evaluate the effect of Strobilanthes crispa ethanol extract (EESC) on body weight in HFD-induced Wistar rats. In this pretest–posttest experimental study, following a 12-week HFD induction, rats were randomly assigned to four groups (n = 6/group): vehicle control, atorvastatin (20 mg/kg BW), EESC-400 (400 mg/kg BW), and EESC-600 (600 mg/kg BW). Treatments were administered orally for 28 days, and body weight was recorded on Days 0, 7, 14, 21, and 28. Repeated measures ANOVA revealed significant effects of time (F = 28.316, p < 0.001, partial η² = 0.586) and time × group interaction (F = 17.163, p < 0.001, partial η² = 0.720), whereas the main effect of group was not significant (F = 1.983, p = 0.149). The greatest mean reduction in Δ body weight was observed in the EESC-400 group (−8.33 g), followed by the EESC-600 group (−6.67 g). The Kruskal–Wallis test demonstrated significant differences in Δ body weight among the experimental groups (H = 16.187, p = 0.001). Bonferroni-adjusted pairwise comparisons revealed significant differences between the vehicle group and the EESC-400 (p = 0.002) and EESC-600 (p = 0.006) groups. In conclusion, EESC may reduce body weight in HFD-induced Wistar rats.